Perancangan UI/UX pada website Arttrash menggunakan metode Design Thinking - Agnestisia, Amelliandha Evifania; Wenas, Michael Bezaleel; Pratiwi, Peni (AITI, 2024)
Appearance covid-19 influenced Arttrash, one of the Salatiga MSMEs engaged in selling miniature waste recycling, because it caused Arttrash to reduce its production capacity so that people worried that Arttrash would be forgotten. This study discusses designing a UI/UX-based website as a promotional medium for Arttrash to expand its business share. UI/UX was designed using the method of design thinking, which realizes the value of environmental preservation based on the use of raw materials from waste—using a qualitative approach to get the problem faced. The result UI/UX was evaluated using the method of usability testing. The result is that design thinking maximizes the design of the UI/UX website Arttrash for help in understanding the target user so that users feel comfortable and easily explore the website Arttrash.